Extractivism, Transnational Capital and Subaltern Struggles in Latin America - López, Emiliano (2015)
Development projects at the national level in Latin American countries are linked with the needs of global transnational extractive-rentier capital accumulation. The concept of unequal geographic development is useful for understanding the articulation between the strategies of transnational capital in the extraction of minerals, hydrocarbons, and agri-foods and the national-scale development projects expressed in the political and economic configurations of the states of the region. This articulation must be approached in terms of the conflictive relations between dominant and subaltern actors and the way in which they are expressed in the structure of the state. Analysis of three concrete cases of subaltern struggles against the strategies of extractive-rentier transnational capital (Peru, Ecuador, and Argentina) reveal the limits and possibilities of transcending local-level disputes to produce a development project that is an alternative to extractivism on the national and continental levels.